Economics of the Caribbean basin - Connolly, Michael B. ed. (Praeger Publishers New YorkUS, 1985)
Contains articles on liberalization policy with specific reference to tax policy in a small, open, developing economy. Shows how to liberalize such an economy. Discusses the debt problem and policy in Latin America. Contains three chapters on capital flows and monetary policy. Examines government policy in Haiti, Jamaica, Costa Rica, and Caribbean Basin economies. Analyses exchange rate policy.